2018
DOI: 10.20897/jisem/2654
|View full text |Cite
|
Sign up to set email alerts
|

Elements of Digital Transformation in Dynamic Capabilities in a Brazilian Capital

Abstract: The objective of the article was to describe the use and importance of elements of digital transformation (IoT, Big Data and Artificial Intelligence) as support for processes of dynamic capabilities in organizations of a Brazilian capital. A research is characterized as exploratory and descriptive, with a quantitative approach. 53 questionnaires were selected from business managers and IT managers. It has been identified that in the perception of business and IT managers the elements of digital transformation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…IT systems are essential for operations and for predicting trends in a fast-changing economy. In line with the literature, the effective spread of IT competencies by government digital transformation support policies not only enhances the overall performance of SMEs but also promotes their organisational ambidexterity (Bustinza et al , 2019; Duchek, 2020; Mendonça and Andrade, 2018; Zawawi et al , 2017).…”
Section: Discussionsupporting
confidence: 72%
“…IT systems are essential for operations and for predicting trends in a fast-changing economy. In line with the literature, the effective spread of IT competencies by government digital transformation support policies not only enhances the overall performance of SMEs but also promotes their organisational ambidexterity (Bustinza et al , 2019; Duchek, 2020; Mendonça and Andrade, 2018; Zawawi et al , 2017).…”
Section: Discussionsupporting
confidence: 72%
“…The need for communication motivates readers to the communication activities, which in essence is a movement of senses in social space. Such communication through game journalism is able to meet the communication needs of the audience only if it is recognized by the players as a lack of knowledge and skills [12- [14][15][16][17]. Video game journalism is primarily considered as recreational, which implies a wide participation of video game journalism in the creation of services for recreation.…”
Section: Resultsmentioning
confidence: 99%
“…From this point, the study of (Fenech et al, 2019;Demir, 2019;Vardarlier & Ozsahin, 2021) recommended the necessity of adopting the digital transformation of human resources in contemporary business organizations. Meanwhile, the study of (Bresciani et al, 2021;Matarazzo et al, 2021) indicated that the digital transformation of human resources increases the ability of the change processes that have a strategic nature and provides flexible business models that have the ability to respond to complex and dynamic environment variables (Mendonça & Andrade, 2018;Cannas, 2021). The study of (Garza, 2013;Batista & Francisco, 2018;Ivory & MacKay, 2020) also indicated that achieving the organizational strategic sustainability requires organizations to make more efforts and launch targeted initiatives towards the environment in which they operate (Amui et al, 2018;Sroufe, 2017).…”
Section: The Problem Of the Studymentioning
confidence: 99%